경호경비조직의 멘토링기능이 경력개발 및 조직유효성에 미치는 영향 - 유영창(Young-Chang Yoo); 김효준(Hyo-Joon Kim); 김찬선(Chan-Sun Kim) (한국콘텐츠학회 논문지, 11(6), 2011)
The Purpose of this study was to examine effects of mentoring function on career development and organizational effectiveness in private security service organization. Example number used on interpretation finally using purposive sampling method after this study establishes 5 places private security service company's security guard by population in Seoul on March, 2010 is total 227 people. Reliability of questionnaire appeared Cronbach's ${α}$ value more than .667. Conclusions that appears in this study is as following. First, private security service organization's Mentoring function affects in career development. That is, if friendship, patronage, career management, society mind, and role model are mobilized, innovative own development, special capacity development, and information competitive power development are helped. Second, private security service organization's Mentoring function affects in organization effectiveness. If friendship, patronage, career management, society mind, and role model are mobilized, career satisfaction, organization immersion, and job satisfaction increase. On the other hand, change of jobs intention decreases if function of society mind is mobilized. Third, private security service organization's career development affects in organization effectiveness. If reform and special capacity development are helped, career satisfaction, organization immersion, and job satisfaction increase. While change of jobs intention decreases as development of information competition is helped. Fourth, Mentoring function exerts influence of causality on career development and organization effectiveness. That is, Mentoring exerts direct influence on organization effectiveness, but it exerts indirect effect through career development. 이 연구의 목적은 경호경비조직의 멘토링기능이 경력개발 및 조직유효성에 미치는 영향을 규명하는데 있다. 이 연구는 2010년 3월 서울소재 5개소 경호경비회사의 경호경비원을 모집단으로 설정한 후 유의표집법을 이용하여 최종분석에 이용된 사례 수는 총 227명이다. 설문지의 신뢰도는 Cronbach's ${α}$값이 .667이상으로 나타났다. 결론은 다음과 같다. 첫째, 경호경비조직의 멘토링기능은 경력개발에 영향을 미친다. 즉, 우정 보호, 경력관리, 사회심리, 역할모델 기능이 발휘되면, 혁신적 자기 개발, 전문능력 개발, 정보경쟁력개발은 촉진된다. 둘째, 경호경비조직의 멘토링기능은 조직유효성에 영향을 미친다. 즉, 우정 보호, 경력관리, 사회심리, 역할모델 기능이 발휘되면, 경력만족, 조직몰입, 직무만족은 증가한다. 반면, 사회심리적기능이 발휘되면 이직의도는 감소한다. 셋째, 경호경비조직의 경력개발은 조직유효성에 영향을 미친다. 즉, 혁신적, 전문능력 개발이 촉진되면, 경력만족, 조직몰입, 직무만족은 증가한다. 반면, 정보경쟁력 개발이 촉진될수록 이직의도는 감소한다. 넷째, 멘토링기능은 경력개발 및 조직유효성에 인과적 영향을 미친다. 즉, 멘토링기능은 조직유효성에 직접적으로 영향을 미치지만, 경력개발을 통해서 간접적인 영향을 미친다.